Emotion Regulation and Academic Stress Correlation Among Senior High Students: Korelasi antara Regulasi Emosi dan Stres Akademik di Kalangan Siswa Sekolah Menengah Atas - Firdausi Nuzula; Effy Maryam (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Academic demands frequently generate psychological pressure among secondary school students, making emotional management an essential personal resource. Specific Background: Numerous educational psychology studies indicate that difficulties in regulating emotions are associated with heightened academic stress symptoms in learning environments. Knowledge Gap: However, empirical evidence focusing on senior high school students within the local school context remains limited and requires systematic quantitative verification. Aims: This study aimed to examine the relationship between emotion regulation and academic stress among students using a correlational design. Results: Statistical analysis demonstrated a significant negative association, indicating that students with better emotional control reported lower stress levels, while weaker regulation corresponded with higher tension and academic burden. Novelty: The study provides context-based data derived directly from high school learners and integrates standardized psychological scales to quantify both constructs simultaneously. Implications: Findings offer practical guidance for counseling services, classroom management, and student support programs to prioritize emotional skills training as a preventive strategy against learning-related stress, contributing to educational psychology literature and school-based mental health initiatives. Keywords: Emotion Regulation, Academic Stress, High School Students, School Counseling, Educational Psychology Key Findings Highlights significant inverse association between emotional control and pressure levels learners with poor coping strategies showed higher tension scores results support counseling interventions in school settings